Pengembangan Etno-Ecotourism pada Taman Nasional Komodo Kabupaten Manggarai Barat - Nasriani Imur; St. Junaeda (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to determine the efforts of the Culture Office in developing ethno-ecotourism in the Komodo National Park, West Manggarai Regency. To achieve this goal, the researchers used data collection techniques obtained by field research through observation, interviews, and documentation. This study used a qualitative research type which was analyzed descriptively to find out the Cultural Office's Efforts in Ethno-Ecotourism Development in Komodo National Park, West Manggarai Regency. The results of field research show that: (1) The development of ethno-econourism in the Komodo National Park is carried out by the community and the management of the Komodo National Park. In the development of ethno-ecotourism is very concerned because it brings benefits to the regional economy and helps the economy of local communities and is able to create an economic boom in which regional income is growing. The West Manggai cultural office establishes training programs related to improving people's skills with the aim of being able to support human resources in West Manggarai. (2) The development of ethno-ecotourism cannot be separated from the supporting and inhibiting factors. Supporting factors are natural potential, cultural potential and human potential. And the inhibiting factor for ethno-ecotourism in Komodo National Park is related to the lack of human resources in the local community who do not fully understand the concept of developing ethno-ecotourism.